Valium without dependence? Individual GABAA receptor subtype contribution toward benzodiazepine addiction, tolerance, and therapeutic effects - Cheng T (Dove Medical Press, 2018)
Tianze Cheng,1 Dominique Marie Wallace,2 Benjamin Ponteri,1 Mahir Tuli3 1Pitzer College, Claremont, CA, USA; 2Portland State University, Portland, OR, USA; 3University of British Columbia, Vancouver, BC, Canada Abstract: Benzodiazepines are one of the most prescribed medications as first-line treatment of anxiety, insomnia, and epilepsy around the world. Over the past two decades, advances in the neuropharmacological understanding of gamma aminobutyric acid (GABA)A receptors revealed distinct contributions from each subtype and produced effects. Recent findings have highlighted the importance of α1 containing GABAA receptors in the mechanisms of addiction and tolerance in benzodiazepine treatments. This has shown promise in the development of tranquilizers with minimal side effects such as cognitive impairment, dependence, and tolerance. A valium-like drug without its side effects, as repeatedly demonstrated in animals, is achievable. Keywords: benzodiazepines, subtype, tolerance, dependence, anxiolytic, GABAA receptor